Restoring the African origins of philosophy - Socrates Ebo (Cхід, 2018)
The standard bias is that philosophy originated in Miletus, in the Greek province of Ionia in Asia Minor. The bias also upholds Thales, a citizen of Miletus to be the first human ever to engage in formal philosophy. The creed of the bias is that the blessings of philosophy spread to the rest of the world from this salvific Greek city. The world owe it to the ingenuity of the Greeks, the appearance of philosophy and science as formal enterprises of learning. This is the “truth”, at least according to mainstream Western literature. Abundance of documentary evidence stating otherwise did not matter. It did not matter also that Thales himself travelled to Egypt and spent many years there, studying philosophy. It did not matter also, that Thales merely reechoed in Ionia, the teachings he received from the school he attended in Egypt. But facts are sacred; biases are optional. Philosophy, indeed had been formally taught in Egypt for thousands of years before Thales ever travelled to Egypt. Literature abounds to that effect. However, the Greeks played a pivotal role in the spread of philosophy to the rest of Europe. The Greeks were the first European nation to philosophize. But that did not amount to the origin of philosophy. It was an epoch in the spread and popularization of philosophy. The fall of Egypt to the invading armies of Alexander the Great, the edits of emperors Theodosius and Justinian of the Roman empire, the invasion of Islam, the slave trade, the experience of colonialism and the subsequent racism changed all that. Africa came to be denigrated as the “Dark Continent”, and as such was deemed incapable of culture and intellectual advancement. This bias significantly influenced, and has arguably continued to colour Western discourse on African themes, covertly and overtly. African intellectuals and researchers all over the world, owe it to posterity, the duty to render the truth about the origins of philosophy. This research relies solely on library research in unearthing oft neglected classical documents that point abundantly to the African origin of philosophy.